Development of typing methods based on pyrosequencing technology fot the analysis of six bovine genes related to marbling - Ripoli, María Verónica (2013)
Several methods such as PCR-RFLP, OLA, DNA sequencing, PCR-SSCP and ARMS-PCR have been developed to detect the allelic variation at substitutions K232A of DGAT1, GH6.1 of GH, F279Y of GHR, R4C of LEP, I74V of FABP4, and at the transition in the TG 5´ leader sequence. Most of these methods are manual processes and therefore increase the time spent on the assay and limit the number of animals analyzed. Herein, we describe the development of pyrosequencing-based methods for the bovine DGAT1, GH, GHR, LEP, FABP4 and TG genes, whose polymorphisms have been associated with variation in carcass composition. This method was validated by analyzing DNA samples belonging to the Aberdeen Angus and Hereford breeds previously typed by PCR-SSCP, PCR-RFLP and/or DNA sequencing. The results obtained showed that, after sequencing or whole-genome association studies (discovery step), the pyrosequencing-based technique seems to be useful to validate (validation step) a particular single nucleotide polymorphism (SNP) in a candidate gene in a previously mapped region in independent populations (with different genotypes and/or production systems). We conclude that pyrosequencing may be useful in high-throughput SNP genotyping of candidate genes in breeds of cattle and other animal species, making it a fast and interesting screening method for population or association studies.